2012
DOI: 10.1128/aac.05516-11
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Fitness and Transmission of Macrolide-Resistant Campylobacter jejuni in Its Natural Host

Abstract: Campylobacter jejuni is a major zoonotic pathogen transmitted to humans via the food chain and is prevalent in chickens, a natural reservoir for this pathogenic organism. Due to the importance of macrolide antibiotics in clinical therapy of human campylobacteriosis, development of macrolide resistance in Campylobacter has become a concern for public health. To facilitate the control of macrolide-resistant Campylobacter, it is necessary to understand if macrolide resistance affects the fitness and transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…Third, a large number of genes involved in the heat shock response, motility, and energy metabolism were significantly downregulated in the macrolideresistant mutants, suggesting that the development of macrolide resistance in C. jejuni profoundly impacts Campylobacter physiology and may result in a growth burden and fitness cost. Indeed, several recent studies found that macrolide-resistant Campylobacter shows a significant fitness cost in vitro and in vivo and is outcompeted by susceptible Campylobacter in the chicken host in the absence of antibiotic selection pressure (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Third, a large number of genes involved in the heat shock response, motility, and energy metabolism were significantly downregulated in the macrolideresistant mutants, suggesting that the development of macrolide resistance in C. jejuni profoundly impacts Campylobacter physiology and may result in a growth burden and fitness cost. Indeed, several recent studies found that macrolide-resistant Campylobacter shows a significant fitness cost in vitro and in vivo and is outcompeted by susceptible Campylobacter in the chicken host in the absence of antibiotic selection pressure (41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the multiple-stepwise-selection approach could yield pleiotropic mutations, thus underestimating the importance of the CmeABC-overproducing mutants that also possessed ϳ200 up-or downregulated genes (including the upregulation of genes encoding an SMR pump [Cj1173] and two MFS pumps [CmeG and Cj0035c]), and some of these changes may affect physiology and metabolism (668). The latter offers an explanation regarding the growth burdens and fitness cost of macrolide-resistant campylobacters reported by the groups of Zhang and Yuan (669)(670)(671). Additional pumps that are independent of CmeABC and CmeEFG also likely mediate MDR (16) but remain to be further studied.…”
Section: Campylobacter Sppmentioning
confidence: 99%
“…However, the spread of resistant bacterial strains still occurs even though resistance can be costly in terms of bacterial fitness (23)(24)(25). In addition, not all resistance carries fitness cost (26,27), and the fitness cost can be ameliorated by compensatory mutations (22,28).…”
Section: Introductionmentioning
confidence: 99%